Efeito do laser de baixa pot??ncia sobre c??lulas musculares C2C12 submetidas ?? les??o por veneno da serpente Bothrops jararacussu. - Silva, Camila Aparecida Alves da (2012)
The venom of snakes of the genus Bothrops, induces an intense inflammatory reaction that leads to develop local tissue necrosis. The serum therapy is efficacious in neutralizing the systemic effects, but its action does not extend the local manifestations. The low power laser (LPB) is used in situations of muscles damage, due to its biological effects, such as analgesics, anti- inflammatory and healing. Thus, the objective of this study was to analyse the effect of LPB in C2C12 muscle cells subjected to injury by Bothrops jararacussu venom by: cell viability, monolayer integrity and release of CK and LDH enzymes. The cells received the venom (12.5 ??l/mL) and were irradiated immediately with LBP Aluminum Gallium Indium phosphorus and Aluminium gallium arsenide, wavelength (??) 685 nm and 830 nm, energy density of 4Jcm2, potency of 100 mW, total energy 1.3 J, exposure time of 13 sec point and the cells were incubated for 15, 30 and 60 minutes. The results showed that the venom affected the viability and integrity of muscle cells in a dose-dependent manner, being chosen the dose of 12.5 ??l/mL for the realization of experiments with the LBP. The LBP caused a significantly increased in cell viability at all times analyzed at ?? 830 nm, however the LBP in the ?? at 685 nm was effective only at 15 and 30 min. The LBP decreased the release of CK and LDH in all time analyzed and with two wavelengths used. However, the LBP was unable to protect cells against cell detachment caused by venom. Thus, this study has shown that the LBP was able to protect the C2C12 muscle cells against the myotoxic effect of B. jararacussu venom and this protection is related to the protective effect of cell membrane. Furthermore, the results obtained suggest that the LBP can be considered a therapeutic tool in patients bitten by bothropic snakes.